The effect of emotional intelligence on job satisfaction: a case study in education - Özer, Aslıhan; Dede, Nazan; Yıldırım, Osman (Int Scientific Conference SGEM, 14, Kilment Ohridsky Blvd, Sofia, 1797, Bulgaria, 2008)
The importance of understanding Emotional intelligence (EI) skills has gravitated form the business management to training activities. The increasing number of recent researches oil this relatively new subject have been tried to investigate its relationships to miscellaneous well-known concepts. Thus, this study aimed at exploring the relationship between one of those well-known concepts, job satisfaction, and emotional intelligence. To this end, a research has been conducted oil the academic personnel (n=82) of four foundation universities in Istanbul. In the research, participants emotional intelligence was assessed by the Emotional Competence Inventory (ECI, 2nd Version) developed by Boyatzis and Goleman. According to the results, a weak relationship (r<0,40) was revealed between emotional intelligence and job satisfaction. Oil the other hand, one of the four dimensions of emotional intelligence, "self management", was found to be strongly related (r>0,40) to the job satisfaction.
Keywords: emotional intelligence; job satisfaction; assessment